1990
DOI: 10.1136/bmj.301.6764.1303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thiazide on rates of bone mineral loss: a longitudinal study.

Abstract: Objective-To determine the effect of thiazide diuretic drugs on rates of bone mineral loss.Design-Longitudinal, observational study with a mean follow up of five years.Setting-Hawaii Osteoporosis Center, Honolulu. Subjects-1017 Japanese-American men born between 1900 and 1920, of whom 378 were treated for hypertension (study group) and 639 did not have hypertension (control group)+ Intervention-Thiazide diuretics were taken by 325 men for a mean of 11.9 years; 53 men took antihypertensive drugs other than thia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(33 citation statements)
references
References 11 publications
1
31
0
1
Order By: Relevance
“…[1][2][3][4][5] Several antihypertensive drugs, including thiazides, b-blockers and angiotensin-converting enzyme inhibitors, decreased the risk of bone fractures and increased bone mineral density (BMD) clinically. [6][7][8][9][10] However, meta-analysis of observational studies on the effects of antihypertensive drugs on fracture outcomes demonstrated no significant association between fractures and calcium channel blockers (CCBs). [11][12][13] CCBs are divided into several subtypes, and non-dihydropyridinetype CCBs, but not dihydropyridine-type CCBs, are reported to reduce the risk of bone fractures through the inhibition of hyperparathyroidism-induced calcium uptake into osteoblasts and an elevation of intracellular calcium in osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Several antihypertensive drugs, including thiazides, b-blockers and angiotensin-converting enzyme inhibitors, decreased the risk of bone fractures and increased bone mineral density (BMD) clinically. [6][7][8][9][10] However, meta-analysis of observational studies on the effects of antihypertensive drugs on fracture outcomes demonstrated no significant association between fractures and calcium channel blockers (CCBs). [11][12][13] CCBs are divided into several subtypes, and non-dihydropyridinetype CCBs, but not dihydropyridine-type CCBs, are reported to reduce the risk of bone fractures through the inhibition of hyperparathyroidism-induced calcium uptake into osteoblasts and an elevation of intracellular calcium in osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…Because it was also observed that expression of calcium transport proteins such as calcium channel TRPV5 and calbindin-D 28K was reduced, it was concluded that another potential explanation is that hypocalciuric effects of thiazides are due to extracellular volume contraction. This secondary effect of thiazides constitutes the basis for their use in treatment of calcium stone disease and may also explain protective effects of thiazides in osteoporosis (333,361,428). In addition, TSC indirectly modulates potassium and acid-base metabolism because secretion of these ions in renal collecting tubule is affected by NaCl delivery to this region of nephron.…”
Section: A Thiazide-sensitive Namentioning
confidence: 99%
“…108,109 Thiazide diuretics which cause a reduction in calcium excretion when given to men and women with and without hypertension reduce the number of hip fractures. 110,111 Inasmuch as kidney stones are known to be associated with a raised urinary excretion of calcium it is probable that the salt-induced increase in urinary calcium excretion in SHR and essential hypertension contributes to their greater incidence of renal stones. [112][113][114] Conclusion: In normal humans salt intake influences urinary calcium excretion and bone turnover.…”
Section: Bone Density and Renal Stonesmentioning
confidence: 99%